Broadcasting real time information using mobile and internet tehcnology on Malaysian super league live score application - Ahmad Faiz, Ilyas (2013)
Currently, almost all Malaysian have interest on football. If the game is promoted properly in Malaysia, we can produce a new generation who are committed towards this sport and become a fan and supporters for Malaysia. To develop the interest toward this sport, a platform which functions as a mediator between the fans and the sports events is needed. The need of user to know about the results of football tournament is fulfilled by the system. Moreover, the system enables the results reach users through SMS alerts. Besides that, it creates medium for sharing through its discussion board features. This feature helps users to point out their thoughts and opinions about football sport in a good way. This web based application is a bridge for the users to the football world. This project use Agile methodology to implement the development process. For the project development, PHP language been used as a language and MYSQL as a database to store information.